2020
DOI: 10.3390/s20247057
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of a Manufactured Bell Using a 3D Scanning Process

Abstract: Bells as percussion instruments have been known to humanity for ages. The casting process, the shape and the materials have changed over the years. The functional properties of bells depend on the casting quality and the generated sound. The casting quality is related to the shape, material and technology. The acoustic quality must fulfill specific parameters. This work concerns the assessment of the quality of the manufactured bells and the possibility of replacing tin bronze with a material with similar mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This method has been widely used in the field of campanology for analysing bell modes [15], for exploring new bell designs, including the major third bells [20], as well as for several other purposes on the bellfounding industry. However, apart from recent studies [21,22], reverse engineering techniques, combining 3D imaging technologies with FEM for the study of bells are still scarcely existent in the literature. In this work we explore this powerful combination to achieve a virtual model as close as possible to the real bell.…”
Section: Numerical Approachmentioning
confidence: 99%
“…This method has been widely used in the field of campanology for analysing bell modes [15], for exploring new bell designs, including the major third bells [20], as well as for several other purposes on the bellfounding industry. However, apart from recent studies [21,22], reverse engineering techniques, combining 3D imaging technologies with FEM for the study of bells are still scarcely existent in the literature. In this work we explore this powerful combination to achieve a virtual model as close as possible to the real bell.…”
Section: Numerical Approachmentioning
confidence: 99%
“…The quality of cast bells is assessed using their acoustic properties, vibrations, and frequency analysis. The acoustic vibrations are also affected by the present porosity and structure of the cast alloy [36].…”
Section: Bronze Alloys and Temple Bellsmentioning
confidence: 99%
“…Al-bronze is characterized by an excellent hardness and strength. Previous authors have shown that castings made of CuSn20 and CuAl10Fe3Mn2 have similar acoustic vibrations, which can be used to develop cheaper and high-strength bell templates that can facilitate the desired curvature shape and acoustic characteristics without further additional tuning [36,62,79].…”
Section: Microstructure Of Bronze Bellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such tasks can be resolved by means of using laser additive technologies. In recent years, several research groups reported case studies where different 3D printing techniques were used, but all known works are not systematic [4][5][6]. The purpose of this work is to demonstrate the principal possibility of the application and benefits of the use of end-to-end 3D scanning technologies and the reproduction of scan results using CNC and 3D printers with a laser source for repairing and reconstructing cultural heritage objects.…”
Section: Introductionmentioning
confidence: 99%